Entamoeba histolytica acetyl-CoA synthetase: biomarker of acute amoebic liver abscess - Lim, Boon Huat; Alfonso, Olivos Garcia; Tan, Zi Ning; Wong, Weng Kin; Noordin, Rahmah; Anaqi Azham, Siti Shafiqah; Lee, Zhi Jie; Guee, Cher Ching; Foo, Phiaw Chong; Pim, Chau Dam (Elsevier, 2014)
Objective: To characterize the Entamoeba histolytica (E. histolytica) antigen(moribound amoebic liver abscess hamsters. s) recognized by Methods: Crude soluble antigen of E. histolytica was probed with sera of moribund hamsters isnp e1cDtr-o manedtr y2 Da-naWlyessitse.r nT hbel octo arrneaslpyosnesd.i nTgh eg eannet iwgeansi cc lopnroetde iann wd aesx pthreenss esden itn f oErs ctahnerdiecmhi am caoslsi BprLo2t1e-inA.I to produce the recombinant E. histolytica ADP-forming acetyl-CoA synthetase (EhACS) recombinAa nctu psrtootmeiins.ed ELISA was developed to evaluate the sensitivity and specificity of the Results: A ~75 kDa protein band with a pI value of 5.91-6.5 was found to be antigenic; and not dtheete pctreodte biny tsoe rbae o tfh hea 7m7s tkeDrsa iEn . thheis tcoolnyttricoal gAroDuPp-. fToramndinegm amceatsysl -spCeocAt rsoymnetthreyt aasnea l(yEshisA rCeSv)e. aTlhede icnufsetcotmedi s(end= 3E1L) aISnAd croensutrlotsl grreovuepa lheadm 1s0te0r%s (sne=n5s)i stievriutym asnadm p10le0s%, rsepsepceicftiicvietyly .w hen tested against Conclusions: This finding suggested the significant role of EhACS as a biomarker for moribund shtaumdisetse resx pwliothre athcue tpeo atemnotieabl irco lleivs eorf aEbhsAcCeSss i n(A bLeAtt)e rin ufnecdteirosnta. nItd iinsg d teheem peadth pogeertnineseinst o tfh AaLt Afu; taunrde in the development of vaccine and diagnostic tests to control ALA in human populations.